SAKK 21/12: a phase II trial of transdermal CR1447 in breast cancer patients. Issue 1 (14th March 2022) - Vetter, Marcus; Rothgiesser, Karin M; Li, Qiyu; Hawle, Hanne; Schönfeld, Wolfgang; Ribi, Karin; Riniker, Salome; von Moos, Roger; Trojan, Andreas; Kralidis, Elena; Fehr, Mathias; Müller, Andreas; et al.
Abstract : Objective: CR1447, a novel transdermal formulation of 4-hydroxytestosterone, has aromatase-inhibiting and androgen receptor (AR)-modulating properties (IC50 4.4 nM) with antitumor effects against AR-positive tumor cells in vitro. This trial investigated the efficacy and safety of CR1447 for patients with metastatic estrogen receptor-positive (A) and AR-positive triple-negative breast cancers (B). Design and methods: (A) included patients with at most one prior endocrine therapy line without progression ≥6 months, whereas (B) included patients with ≤2 prior chemotherapy lines, all displaying advanced signs of disease. The primary endpoint was disease control at week 24 (DC24). The null hypothesis was DC24 ≤30% (A) and ≤15% (B). Thirty-seven patients were recruited (29 in (A) and 8 in (B)); accrual was stopped following an interim analysis demonstrating futility in (A) and slow accrual in (B). Results: DC24 was attained in 5/21 (95% CI: 8.2–47.2) patients in (A) and none in (B). The median progression-free survival was 5.1 months (95% CI: 2.5–5.6) in (A) and 2.5 months (95% CI: 0.7–2.6) in (B). The median overall survival was 24.6 months (95% CI: 22.9–not applicable) in (A) and 10.8 months (95% CI: 3.3–10.9) in (B). CR1447 had a favorable safety profile without treatment-related grade 3–5 toxicities in (A). Especially no side effects linked to androgenic effects were observed. Conclusions: Despite this trial being negative, the 24% DC24 rate in a second-line setting, and the prolonged partial response experienced by a patient, indicate activity. Further evaluation of CR1447 in endocrine-sensitive patients or combination trials appears warranted.